PENGARUH PENGGUNAAN MEDIA GRAFIS TERHADAP HASIL BELAJAR MATA PELAJARAN BAHASA INDONESIA SISWA SEKOLAH DASAR NEGERI 55 PAREPARE - Halik, Abd; Hakim, Abdul (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2020)
This study examines the presence or absence of the influence of using graphic media on learning outcomes in Indonesian subjects. The formulation of the problem studied is whether there is an influence of the use of graphic media on student learning outcomes in Indonesian subjects, namely the ability to read comprehension in the material types of characters in fiction. This study aims to determine the effect of using graphic media on learning outcomes in Indonesian subjects. This research uses a quantitative approach to the type of experimental research and uses pre-experimental design in the form of one-group pretest-posttest design. The sampling technique used in this study is the Non Probability Sampling technique with a sample size of 23. The data collection technique used in this study is a test of learning outcomes and documentation. The data analysis technique used in the study is a t-test to test the hypothesis preceded by the analysis prerequisite test in the form of a normality test. The results of hypothesis testing using the Paired Sample T-test which shows Sig (2-tailed) <0.05 so that H0 is rejected and Ha is accepted which means that the graphic image learning media has a good effect because it improves the learning outcomes of Indonesian about reading comprehension of fourth grade students public elementary school 55 Parepare.